Percepatan Pemulangan Pasien Rawat Inap dengan Konsep Lean di Rumah Sakit Masmitra - Alamsyah, Alamsyah (Jurnal ARSI : Administrasi Rumah Sakit Indonesia, 2017)
The process discharge of patients in hospital Masmitra is still not optimal, because there is no groove that describes the process of returning the patient as a whole. By applying the concept of Lean, value stream mapping current conditions which shows that the process of returning patients there were 41 activities and only 51% are value added, and of course has implications for wastage. From the analysis of the root causes of acquired ideas repair, and then carried into the re-design of the new process flow is considered ideal to produce a total of only 17 activities, 83% of which is value added. With the implementation of Lean Concept in RS Masmitra, expected efficiency will also occur when the work is done in accordance with what is required by the patient, right time, the right size and right on target.